Outcome of Pediatric Patients with Fracture of Femur Fixed with Intramedullary Elastic Nail - Saifullah Soomro, Asif Ali Shaikh, Zamir Ahmed Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the effects of elastic intramedullary nails used for fixation of femur diaphyseal fractures in paediatric patients. Method: This prospective observational research was done from April 2020 to June 2021. 52 paediatric patients diagnosed with femur diaphyseal fractures with mean age from 6 to 12 years were enrolled in this study. All patients were admitted and subsequently operated for treatment of femur fracture using elastic intramedullary nail in retrograde fashion. Patients were in structured follow up till radiological union realized. Flynn scoring criteria was applied to evaluate the functional outcomes at 6 months after surgery. Results: The average age of patient enrolled was 9 years (6- 12 years), all 52 patients were in follow up for average 26 weeks (14-36 weeks). Fracture union was observed in all operated children in mean time of 9 weeks (range 6-12 weeks). Four participants suffered superficial skin infection at entry site. Two patients had limb length discrepancy upto1.5cm and two patients had varus angulations up to (10º) and in two patients proximal migration of nail was noted. According to Flynn Criteria outcome was excellent in 38 patients (73.1%), satisfactory in 12 patients (23.1%), poor in 2 patient (3.8%) respectively Conclusion: Fixation of femoral diaphyseal fracture with intramedullary elastic nail in paediatric patients is better option. One can achieve excellent results, satisfactory radiological and clinical bony union, with lowest complication rate, so it could be regarded as a favorable fixation implant for management of diaphyseal femur fractures in pediatric age group. Keywords: Fracture, femur shaft, elastic intramedullary Nail, Paediatric patients.